2009
DOI: 10.1007/s10764-009-9354-1
|View full text |Cite
|
Sign up to set email alerts
|

Daily Energy Balance and Protein Gain Among Pan troglodytes verus in the Taï National Park, Côte d’Ivoire

Abstract: Energy balance and protein gain contribute significantly to an animal's survival. Although data are available for certain species in captive settings, there is little information on these factors for primates living in their natural environments. In this preliminary study, we combined detailed behavioral, phonological, and chemical data for a well habituated chimpanzee community from the Taï National Park, Côte d'Ivoire, with estimates of energy gain and expenditure from captive chimpanzees and humans to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 46 publications
4
30
0
Order By: Relevance
“…The energy balance was estimated using similar methods as described in ref. 57; see Supporting Information for details. We only analyzed data from days that followed complete observation days (from nest departure to nest building) so that the relative energy balance could be compared between mornings.…”
Section: Methodsmentioning
confidence: 99%
“…The energy balance was estimated using similar methods as described in ref. 57; see Supporting Information for details. We only analyzed data from days that followed complete observation days (from nest departure to nest building) so that the relative energy balance could be compared between mornings.…”
Section: Methodsmentioning
confidence: 99%
“…There are also situations in which it is difficult to differentiate responses to necessity and opportunity. Adult female chimpanzees in the Tai forest opportunistically exploit Coula edulis nuts with tools during their period of seasonal abundance that could also be a response to necessity as the chimpanzees experienced a negative energy balance on half of the days surveyed [34]. While it is commonly suggested that limited food distribution and abundance may prompt the invention of novel foraging strategies, abundance of resources can also furnish the time and energy to pursue such activities.…”
Section: Introductionmentioning
confidence: 99%
“…c Koops et al [32]. d Gunther & Boesch [33] and N'Guessan et al [34] (necessity: negative energy balance among some community members across seasons; opportunity: nut cracking tool use coincides with abundance of nuts; profitability: energetic gain from nut cracking). e Bogart & Pruetz [35, p. 11] (necessity: based on overall savannah environment rather than negative correlation with staple foods, 'invertebrates are an important source of protein and other essential nutrients in a highly seasonal environment', but termites are a staple component of the Fongoli chimpanzee diet, and their consumption is not correlated with periods of low fruit availability energy needs via other sources.…”
Section: Introductionmentioning
confidence: 99%
“…Protein requirements in chimpanzees have been estimated for growing individuals; 3.5–4.5 g/kg body weight/day for 2.6–6.4‐year‐old individuals with body weights of 10.0–24.1 kg . The estimated protein consumption in wild adult chimpanzees is approximately 60–200 g/day with large variations . It has been estimated that wild Bornean orangutans consume an average of 73.0 ± 33.9 g/day and 54.0 ± 33.6 g/day protein intake during high and low fruit periods, respectively .…”
Section: Discussionmentioning
confidence: 99%